Territorializing spatial data: Controlling land through One Map projects in Indonesia and Myanmar. (October 2022) - Faxon, Hilary Oliva; Goldstein, Jenny E.; Fisher, Micah R.; Hunt, Glenn
Abstract: Once confined to paper, national cartographic projects increasingly play out through spatial data infrastructures such as software programs and smartphones. Across the Global South, foreign donor-funded digital platforms emphasize transparency, accountability and data sharing while echoing colonial projects that consolidated state-based territorial knowledge. This article brings political geography scholarship on state and counter-mapping together with new work on the political ecology of data to highlight a contemporary dimension of territorialization, one in which state actors seek to consolidate and authorize national geospatial information onto digital platforms. We call attention to the role of data infrastructures in contemporary resource control, arguing that territorializing data both extends state territorialization onto digital platforms and, paradoxically, provides new avenues for non-state actors to claim land. Drawing on interviews, document review, and long-term fieldwork, we compare the origins, institutionalization and realization of Indonesia and Myanmar's 'One Map' projects. Both projects aimed to create a government-managed online spatial data platform, building on national mapping and management traditions while responding to new international incentives, such as climate change mitigation in Indonesia and good democratic governance in Myanmar. While both projects encountered technical difficulties and evolved during implementation, different national histories and political trajectories resulted in the embrace and expansion of the program in Indonesia but reluctant participation and eventual crisis in Myanmar. Together, these cases show how spatial data infrastructures can both extend state control over space and offer opportunities for contesting or reimagining land and nation, even as such infrastructures remain embedded in local power relations. Highlights: Territorializing data–the process of bringing geospatial information onto digital platforms under state control–is increasingly important to resource governance. Indonesia and Myanmar's One Map programs illustrate how territorializing data is dependent on existing relations of resource governance and embedded in longer traditions of state-making through mapping. Data infrastructures paradoxically consolidate control while opening opportunities for participation in environmental politics.